x^2 -- x --72
by Middle term distribution method
Anonymous:
___k off
Answers
Answered by
5
Solution:-
Given Quadratic Equation :-
x^2 - x - 72
=) x^2 - x - 72
=) x^2 - ( 9 - 8)x - 72
=) x^2 - 9x + 8x - 72
=) x ( x - 9) + 8( x- 9)
=) ( x - 9) ( x+8)
=) x = 9. and. x= -8.
Answered by
6
It is a method of factorization in which we have to split the middle term in such a way that the addition of new terms is equal to the middle term and multiplication of new terms is equal to the product of 1st & 3rd term.
x² - x - 72
x² - 9x + 8x - 72
x (x - 9) + 8 (x - 9)
(x - 9) (x + 8)
So, the answer is
Similar questions